THE APPLICATION OF ICONIC DESIGN IN THE ARCHITECTURAL FORM OF THE VELODROME SPORT CENTER IN SURABAYA - Aditya Aditya; sigit hadi laksono; Ika Ratniarsih (Faculty of Civil Engeneering and Planning - ITATS, 2026)
The development of iconic architecture has become an essential approach in creating buildings that not only serve functional needs but also embody symbolic identity. The Velodrome Sport Center in West Surabaya is designed as an architectural landmark that reflects the spirit of modern cycling sports while adopting a postmodern theme with a macro concept of hi-tech architecture. The oval form of the building is derived from the transformation of a bicycle helmet, symbolizing speed, safety, and aerodynamic efficiency, making the structure both visually dynamic and contextually meaningful.The research method applies a qualitative-descriptive approach through literature studies on iconic architecture, postmodern theory, and hi-tech principles. Site analysis and conceptual synthesis are conducted to align the design with the physical context, user activity, and symbolic representation. The study emphasizes the relationship between structure, form, and material—particularly the use of exposed structural elements and ACP panel facades that highlight technological expression and aesthetic identity.The result presents a Velodrome design that stands as an architectural icon for Surabaya. The application of an oval dynamic form supported by a hi-tech structural system creates a monumental yet functional space that enhances aerodynamic performance and visual distinctiveness. Through its exposed structure and material expression, the building achieves a strong postmodern identity, representing innovation and symbolizing the progressive image of the city.